Human papillomavirus genotypes associated with cervical neoplasia in India. Issue 4 (1st July 2006) - Peedicayil, A.; Abraham, P.; Sathish, N.; John, S.; Shah, K.; Sridharan, G.; Gravitt, P.
Abstract : The aim of this study was to determine the prevalence of human papillomavirus (HPV) genotypes in tissue with cervical neoplasias in patients from south and east India. Cross-sectional cervical tissue was obtained from 100 patients from south India and 30 patients from east India who had a biopsy for clinically invasive cervical cancer or cervical intraepithelial neoplasia (CIN) in a tertiary care hospital in India. DNA amplification was done with biotinylated PGMY 09/11 primers, and the line blot assay was used to determine the HPV genotype. HPV DNA was detected in 95% of invasive cancers (113/119) and 91% of CINs (10/11). A single HPV type was found in 100 women (77%), and mixed infections were found in 23 women (18%). HPV 16 (60%) and HPV 18 (14%) were the most frequent types, but 16 other types (26, 31, 33, 35, 42, 45, 51, 52, 53, 56, 58, 61, 62, 64, 81, and 82) were also identified. HPV 16 was present in 63% of patients from south India and in 50% of patients from east India, while HPV 18 was present in 12% and 20%, respectively. There are several high-risk HPV types associated with cervical neoplasias of which types 16 and 18 are the most common.